2014
DOI: 10.5505/tjtes.2014.67670
|View full text |Cite
|
Sign up to set email alerts
|

Experience of 80 Cases with Fournier's Gangrene and 'Trauma' as a Trigger Factor in the Etiopathogenesis

Abstract: BACKGROUND:The purpose of the present study was to retrospectively analyze the patients' data presented with Fournier's gangrene (FG), to compare obtained data with the literature and to investigate the role of "trauma" in the etiopathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 76 publications
(96 reference statements)
0
10
0
3
Order By: Relevance
“…Зона поражения резко увеличивается в размерах за счет прогрессирования заболевания и вторичной ин-фекции [113]. Бурное течение ГФ, сопровождающееся резким отеком полового члена и мошонки, может вы-звать затруднение мочеиспускания и даже привести к острой задержке мочеиспускания у 5% больных [53]. В некоторых случаях возможно образование наружного мочевого свища на промежности, полное или частич-ное обнажение яичек после отторжения некротически измененных тканей мошонки [14,113].…”
Section: гангрена фурнье (гф)unclassified
See 2 more Smart Citations
“…Зона поражения резко увеличивается в размерах за счет прогрессирования заболевания и вторичной ин-фекции [113]. Бурное течение ГФ, сопровождающееся резким отеком полового члена и мошонки, может вы-звать затруднение мочеиспускания и даже привести к острой задержке мочеиспускания у 5% больных [53]. В некоторых случаях возможно образование наружного мочевого свища на промежности, полное или частич-ное обнажение яичек после отторжения некротически измененных тканей мошонки [14,113].…”
Section: гангрена фурнье (гф)unclassified
“…С окончанием процесса отторжения тканей наблюдаются репаративные процессы с разви-тием грануляций и краевой эпителизации, после чего на месте отторгнувшихся тканей остаются рубцы, про-исходит деформация половых органов. Однако значи-тельно чаще ГФ без адекватной терапии заканчивается летальным исходом на фоне сепсиса [1,3,15,16,25,26,48,53,51,64,67,112].…”
Section: гангрена фурнье (гф)unclassified
See 1 more Smart Citation
“…Other often-compromised areas are perianal region, inguinal region, abdominal wall, penis, and vulva. [14] In this sense, the selected studies showed that the most important aspect in handling Fournier's Gangrene is identifying and controlling risk factors, as well as the early recognition of the disease. These are ways to ensure the appropriate treatment, minimizing possible complications and promoting life quality for the patient.…”
Section: Demographic Epidemiological and Clinical Aspects Of Patienmentioning
confidence: 99%
“…Whenever necessary, those were supplemented with urinary or fecal diversion, through cystostomies and colostomies, and skin repair. [14,21] Thus, in order to promote an appropriate treatment, it is essential to get multidisciplinary approach for health team, including assessing the injury, which usually features a large extent, by the nurse.…”
Section: Therapeutic Modalities In Treating Fournier's Gangrenementioning
confidence: 99%